The factors that affect the failure of loan repayment in MARA state of Malacca / Nor Fadzillah Ismail - Ismail, Nor Fadzillah (Faculty of Business and Management, 2011)
Loan repayment is an obligation for a borrower who takes any types of loan. The repayment must be on time to avoid it from become outstanding and be penalty by the law. In other way, there are such things that the organization or the company can do to crack this problem. From the past studies, found that there are numerous reasons that affect the loan repayment. This current research study on three factors that could be the reason for the borrowers that fail to repay back their loan namely interest rates, borrowers’ characters and income level. This study has been undertaken to identify the relationship between those factors that cause the failure of loan repayment in MARA State of Malacca and the most factors that contributes to the failure of the loan repayment. Since the data was analyzed by Statistical Package for the Social Sciences (SPSS)version 18, the result showed that the borrowers’ characters have significant relationship with the failure of loan repayment. It also revealed that the income level also have significant relationship with the failure of loan repayment. But then, the interest has weak relationship towards the failure of loan repayment. The result also discloses that the borrowers’ characters are the most factors that contribute to the failure of loan repayment. There are several recommendations also been discussed.